Imaging Methods of Ovarian Fibroma in a 55-year-old Patient - Devic, Aleksandar; Dević, Ana; Sorak, Marija; Zajic, Goran (Medicinski časopis, 2022)
Introduction: We presents a patient aged 55 years, with ovarian fibroma measuring 134x72x112 mm with the associated fallopian tube measuring 55x9mm (previously analyzed ex tempore method). Fibroma is a benign ovarian tumor consisting of fibroblasts, collagen fibers and arising from the ovarian stroma. It accounts for 1% to 5% of all ovarian tumors and occurs in the population aged 20 to 80, and most often after the age of 50. Patient and Methods: On ultrasonographic examination, the uterus swims in about 100 ml of anechoic free fluid. Anteuterine, without a clear connection with the uterus, a larger soft-tissue tumefaction, clearly limited and it seems that it is mobile, measuring 106x80 mm. After that,MSCT and MR of the abdomen and small pelvis were performed. After adequate preparation, the patient underwent surgery and the obtained material was sent for histopathological diagnosis. Results: The analyzed sample consists of tumor proliferation of predominantly spindle cells organized by vertebrates, in some places vortex to zones of somewhat loose structure, focal with collagen and straight fibers. This histological finding is most appropriate for fibroids. clearer preserved histological material. Conclusion: Surgery is the therapy of choice in the treatment of ovarian tumors. Despite the application and availability of all modern diagnostic methods, in this case report, the origin of the tumor was discovered by surgery. From the above, we can conclude that accurate diagnosis of ovarian tumors is extremely difficult. In accordance with that, it is necessary to improve the existing techniques and discover new diagnostic procedures, on the basis of which, in the interest of the patient, the doctor would more easily decide on the adequate treatment of ovarian tumors.